2020
DOI: 10.47291/efi.v66i1.629
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Capital on Shadow Economy in Indonesia

Abstract: Shadow economy is a market for legal and illegal goods and services that escape recording and estimation of GDP. It can cause inaccurate estimation of GDP, declining tax revenue, and less precise economic policies. Improving the quality of human capital, both in education and health dimensions, can reduce shadow economy. The research aims to estimate shadow economy and analyze the influence of the quality of human capital on shadow economy in Indonesia. Applying time series multiple linear regression analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Recent studies by Saraswati and Agustina (2020) and Rezky (2020) indicate that the size of shadow economy is still high. Saraswati and Agustina (2020) stated that the size of shadow economy in Indonesia during the period 1981 to 2014 averaging 29% of gross domestic product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Saraswati and Agustina (2020) and Rezky (2020) indicate that the size of shadow economy is still high. Saraswati and Agustina (2020) stated that the size of shadow economy in Indonesia during the period 1981 to 2014 averaging 29% of gross domestic product.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Saraswati and Agustina (2020) and Rezky (2020) indicate that the size of shadow economy is still high. Saraswati and Agustina (2020) stated that the size of shadow economy in Indonesia during the period 1981 to 2014 averaging 29% of gross domestic product. Their study found that human capital measures by life expectancy mitigate shadow economy; while enrolment in tertiary education induces expansion in shadow economy in Indonesia.…”
Section: Introductionmentioning
confidence: 99%